USING ROLE PLAY TO PORTRAIT THE LEARNING ENGAGEMENT OF THE ELEVENTH GRADERS IN SPEAKING CLASS (RETAIN, 2014)
USING ROLE PLAY TO PORTRAIT THE LEARNING ENGAGEMENT OF THE ELEVENTH GRADERS IN SPEAKING CLASS Irma Deviana English Department, Languages and Arts Faculty, State University of Surabaya dephy.sasoka@gmail.com Dra. Theresia Kumalarini, M.Pd. English Department, Languages and Arts Faculty, State University of Surabaya kumala_rini52@yahoo.co.id Abstrak Berlatih adalah kunci menjadi pembicara yang baik. Faktanya, beberapa siswa tidak berlatih untuk berbicara dalam bahasa inggris pada kegiatan berbicara. Akibatnya, mereka takut untuk mengekspresikan diri dan cenderung tidak berpartisipasi di kegiatan berbicara. Kearsley dan Shneiderman (1999) menyatakan bahwa siswa dengan penuh arti harus terikat dalam kegiatan belajar melalui interaksi dengan yang lain dan tugas yang berguna. Dengan mempertimbangkan hal ini, penelitian kualitatif ini bertujuan untuk mendeskripsikan bagaimana partisipasi siswa dalam kegiatan role play pada kemampuan berbicara. Subjek dari penelitian ini adalah siswa kelas sebelas di SMAN 13 Surabaya. Peneliti memilih 10 siswa sebagai sampel yang diperoleh dari informasi dari guru matapelajaran bahasa Inggris dan mewawancarai mereka kemudian menilainya. Setelah itu, mereka dibagi menjadi dua kategori, proficient dan less proficient. Peneliti mengumpulkan data melalui observation checklist. Kemudian, 10 siswa tersebut diwawancarai untuk memperkuat hasil observasi. Hasil dari penelitian ini menunjukkan bahwa siswa pada kedua kategori sama-sama berpartisipasi dalam kegiatan role play. Hasil dari wawancara menunjukkan bahwa hubungan antar teman menjadi kuat karena mereka bekerja sama selama role play. Oleh karena itu, peneliti menyarankan kepala guru pelajaran bahasa Inggris untuk menggunakan role play sebagai kegiatan berbicara untuk meningkatkan partisipasi siswa dan melatih siswa berbicara bahasa Inggris (Ladousse, 1987). Kata Kunci: Role Play, Partisipasi Siswa, Kegiatan Berbicara Abstract Keep practicing is the key to be a good speaker. In reality, some students do not practice to speak English in their speaking class. Consequently, they are afraid of speaking out and incline not to get involved in speaking class activity. Kearsley and Shneiderman (1999) stated that “students must be meaningfully engaged in learning activities through interaction with others and worthwhile tasks.” Considering this, this qualitative study aims to describe how the students’ engagement is in the implementation of Role Play in speaking class. The subject of this study was the eleventh graders of SMAN 13 Surabaya. The researcher selected ten students as the sample by describing the documentary information from the English teacher and interviewing the students then scoring them using speaking rubric. Afterwards, they were divided into two categories, i.e proficient and less proficient. In conducting the study, the researcher collected the data through observation checklist. Then, she interviewed the ten selected students to confirm the observation. The result showed that both proficient and less proficient students were all engaged in a role play activity. The result of the interview revealed that the relationship among friends was stronger as they worked in a team during the role play. Therefore, the researcher recommends that English teachers use role play as an activity in the speaking class to enhance the students’ engagement and train the students to say the right expression in the right place and at the right time (Ladousse, 1987). Keywords: Role Play, Students’ engagement, Speaking Class Activity INTRODUCTION A wise man ever said, “The more often you speak, the easier it becomes.” It simply means that practice often is the key to be a good speaker. In reality, there are some students especially EFL students who are still afraid of speaking English. Some of them worry to express what is in their mind or always keep thinking that people will not understand them when they are speaking. The reason is because they do not practice to speak English even in their oral class. This happens to students from lowest till highest levels. They get the same treatment where they just have little chance to speak. Besides, when the students get that little chance to speak, they incline not to get involved in speaking activity. Some of them are shy, not willing to share their ideas, and feel unprepared. This occurs due to lack of practice in speaking class. In addition, the condition of education in Indonesia is similar to that of China. Most students’ speaking skill is in the second-rate than other skills such as listening, reading and grammar. It results from getting high scores in the Higher Education Exam as the only purpose of the high school students. There is no speaking English test that is why speaking skill is often ignored. Besides, the students do not have more chance to speak because there are usually over 50 students per class (Jianing, 2007). Since this situation also occurs in Indonesia, the teachers should concern with this phenomenon. In reality, students do not have enough opportunity to practice speaking in class and the speaking skill itself is not taken any notice. It gives a big impact on the students. It makes them unwilling to participate in the activity, which is called the student’s engagement, when it really comes to speaking time. Dealing with the student’s engagement, the idea of engagement is that “students must be meaningfully engaged in learning activities through interaction with others and worthwhile tasks” (Kearsley & Shneiderman, 1999). It simply means that the students must actively get involved in the activity given. By doing so, the students will automatically communicate with other students. This shows that the students have a willing to study, in this case practicing speaking. Therefore, the point of the material will be easily understood by the students. On the contrary, if the students are unwilling to study, they will not have intention to participate in speaking activity. Some of them will just prefer to listen and keep silent or incline to be passive. That condition may prevent learners to have a good speaking performance. Dealing with it, role play is chosen to be a good practicing way in boosting student’s engagement in a speaking class. According to Brown cited by Huang (2008),